Composite board, composite panel, and manufacturing method of the same

A composite board with a low-density gel body and substrate provides enhanced thermal insulation and mechanical strength, addressing the fragility of silica aerogel blocks for improved exterior wall materials.

JP2025078317AActive Publication Date: 2025-05-20KYOTO UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023190790
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-11-08
Publication Date
2025-05-20
Estimated Expiration
2043-11-08

AI Technical Summary

Technical Problem

Existing wall materials, particularly exterior walls, require improved thermal insulation and mechanical strength to meet energy conservation demands, while materials like silica aerogel blocks are fragile and difficult to apply.

Method used

A composite board comprising a substrate and a low-density gel body, such as an aerogel, with a flexural modulus of 4.0 MPa or more and a flexural breaking strain of 0.05 or more, is formed by immersing the substrate in a solution containing a precursor compound, allowing gelation and drying to create a composite board with enhanced mechanical properties suitable for wall materials.

Benefits of technology

The composite board achieves improved thermal insulation and mechanical strength, making it suitable for exterior walls, with a balanced elastic modulus and fracture strain, and can withstand external forces like wind gusts, while maintaining low thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025078317000001_ABST
    Figure 2025078317000001_ABST
Patent Text Reader

Abstract

To provide a member that contains a low-density gel body such as aerogel and is suitable for application to a wall material.SOLUTION: A member provided is a composite board including a substrate and a low-density gel body that is composited with the substrate, and has a flexural modulus of 4.0 MPa or more and a flexural fracture strain of 0.05 or more. The composite board may have a flexural strength of 2.5 MPa or more. The substrate may include at least one selected from the group consisting of glass wool and rock wool.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite board, a composite panel, a method for manufacturing a composite board, and a method for manufacturing a composite panel. [Background technology]

[0002] Sandwich panels, in which a heat insulating foam core is sandwiched between steel plates, are known as exterior wall materials for buildings (for example, Patent Document 1). In addition, although there is no mention of wall materials, Patent Document 2 discloses a block of silica aerogel as a material with low thermal conductivity. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-226010 [Patent Document 2] U.S. Pat. No. 4,402,927 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a strong demand for energy conservation, and there is a strong demand for improving the thermal insulation of wall materials, including exterior walls. Taking note of the low thermal conductivity, it is conceivable to apply the aerogel block of Patent Document 2 to wall materials. However, according to the inventors' investigation, the block is fragile and difficult to apply to wall materials as it is.

[0005] An object of the present invention is to provide a member that contains a low-density gel body such as an aerogel and is suitable for use as a wall material. [Means for solving the problem]

[0006] The present inventors have investigated the formation of a composite between a low-density gel body and a substrate, and have completed the present invention by focusing on mechanical properties suitable for a wall material.

[0007] The present invention relates to The present invention includes a substrate and a low-density gel body composited with the substrate, A composite board having a flexural modulus of 4.0 MPa or more and a flexural breaking strain of 0.05 or more is provided.

[0008] Further, the present invention relates to The composite board; a surface layer disposed on at least one surface of the composite board; A composite panel comprising:

[0009] Further, the present invention relates to A method for producing the composite board, comprising the steps of: forming a wet gel by immersing the substrate in a solution containing a sol of a precursor compound having a hydrolyzable functional group and proceeding with gelation of the sol in a state where the substrate is immersed in the solution; drying the wet gel to form the composite board comprising the substrate and a low density gel body composited with the substrate; The present invention provides a method for manufacturing a composite board, comprising:

[0010] Further, the present invention relates to A method for producing the composite panel, A method for making a composite panel is provided, comprising disposing a surface layer on at least one surface of the composite board. Effect of the Invention

[0011] According to the present invention, it is possible to provide a member that contains a low-density gel body and is suitable for use as a wall material. [Brief description of the drawings]

[0012] [Figure 1] 1 is a perspective view showing a schematic diagram of an example of a composite board of the present invention, and a partially enlarged view of the same. FIG. [Figure 2A] FIG. 1 is a perspective view showing a schematic diagram of an example of a composite panel of the present invention. [Figure 2B]2B is a cross-sectional view showing section 2B-2B of the composite panel of FIG. 2A. [Diagram 3] 2 is a graph showing stress-strain curves obtained by a three-point bending test in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The composite board according to the first aspect of the present invention comprises: The present invention includes a substrate and a low-density gel body composited with the substrate, It has a flexural modulus of 4.0 MPa or more and a flexural fracture strain of 0.05 or more.

[0014] In a second aspect of the present invention, for example, the composite board according to the first aspect has a bending strength of 2.5 MPa or more.

[0015] In a third aspect of the present invention, for example, in the composite board according to the first or second aspect, the substrate is a porous material, and the low-density gel body is present inside the pores of the substrate.

[0016] In a fourth aspect of the present invention, for example, in the composite board according to any one of the first to third aspects, the base material includes at least one selected from the group consisting of glass wool and rock wool.

[0017] In a fifth aspect of the present invention, for example, in the composite board according to any one of the first to fourth aspects, the density of the substrate is 32 kg / m 3 That's all.

[0018] In a sixth aspect of the present invention, for example, in the composite board according to any one of the first to fifth aspects, the low-density gel body has a skeleton including a polyorganosiloxane chain.

[0019] In a seventh aspect of the present invention, for example in the composite board according to the sixth aspect, the polyorganosiloxane chain has T units as main constituent units.

[0020] In an eighth aspect of the present invention, for example, the composite board according to any one of the first to seventh aspects further comprises a filler.

[0021] In a ninth aspect of the present invention, for example in the composite board according to the eighth aspect, the filler is at least one selected from the group consisting of metal hydroxide particles and metal oxide particles.

[0022] In a tenth aspect of the present invention, for example, the composite board according to any one of the first to ninth aspects is used as a wall material for buildings.

[0023] The composite panel according to the eleventh aspect of the present invention is A composite board according to any one of the first to tenth aspects; a surface layer disposed on at least one surface of the composite board; Equipped with.

[0024] In a twelfth aspect of the present invention, for example, the composite panel according to the eleventh aspect is used as a wall material for a building.

[0025] A method for producing a composite board according to a thirteenth aspect of the present invention includes the steps of: A method for producing a composite board according to any one of the first to tenth aspects, comprising: forming a wet gel by immersing the substrate in a solution containing a sol of a precursor compound having a hydrolyzable functional group and proceeding with gelation of the sol in a state where the substrate is immersed in the solution; drying the wet gel to form the composite board comprising the substrate and a low density gel body composited with the substrate; Includes.

[0026] In a fourteenth aspect of the present invention, for example, in the method for producing a composite board according to the thirteenth aspect, the precursor compound is a silicon compound.

[0027] In a fifteenth aspect of the present invention, for example, in the method for producing a composite board according to the thirteenth or fourteenth aspect, the wet gel is dried by drying at normal pressure.

[0028] A method for producing a composite panel according to a sixteenth aspect of the present invention includes the steps of: A method for producing a composite panel according to an eleventh or twelfth aspect, and disposing a surface layer on at least one surface of the composite board.

[0029] [Composite board] An example of the composite board of this embodiment is shown in FIG. 1. FIG. 1 is a perspective view of the composite board 1 and a partially enlarged view of the composite board 1. The composite board 1 includes a base material 2 and a low-density gel body 3. The base material 2 is a board-shaped member. The base material 2 in FIG. 1 is composed of fibers 21 entangled in a three-dimensional direction. The base material 2 has holes (voids) 22 between adjacent fibers 21. The holes 22 extend in a three-dimensional direction inside the base material 2. The low-density gel body 3 exists inside the holes 22 that the base material 2 has. The low-density gel body 3 preferably fills the inside of the holes 22, in other words, may extend in a three-dimensional direction inside the base material 2. In one example of a filled embodiment, the composite board 1 has a region in which the low-density gel body 3 is continuous across its thickness direction, in other words, from one main surface 23 to the other main surface 24. Alternatively or in addition, the composite board 1 may have a region in which the low-density gel body 3 is continuous from one end to the other end in the planar direction of the composite board 1. The base material 2 and the low-density gel body 3 contained in the composite board 1 cannot be separated and each retains its shape. In other words, the base material 2 and the low-density gel body 3 are composited.

[0030] The composite board 1 has a flexural modulus of 4.0 MPa or more and a flexural fracture strain of 0.05 or more. According to the inventors' studies, when applying to wall materials, particularly exterior walls, it is important to ensure the elastic modulus and fracture strain in the bending direction. The elastic modulus contributes to the self-supporting ability of the wall material and to reducing deflection that may occur due to external forces. The fracture strain contributes to ensuring "toughness" to resist gusts of wind such as typhoons. The composite board 1 having a flexural modulus and bending fracture strain equal to or greater than a predetermined value is suitable for application to wall materials, even though it contains a low-density gel body 3.

[0031] The flexural modulus may be 5.0 MPa or more, 8.0 MPa or more, 10 MPa or more, 11 MPa or more, 12 MPa or more, 13 MPa or more, or even 14 MPa or more. The upper limit of the flexural modulus is, for example, 75 MPa or less.

[0032] The bending fracture strain may be 0.06 or more, 0.07 or more, 0.08 or more, or even 0.09 or more. The upper limit of the bending fracture strain is, for example, 0.20 or less.

[0033] The flexural modulus and bending fracture strain can be determined from the stress-strain curve obtained by a three-point bending test. The shape of the test piece is usually a rectangular parallelepiped, and its size is, for example, 50 mm in length x 10 mm in width x 5 mm in thickness. The test speed is 10 mm / min, the distance between the supports is 40 mm, and the radius R1 of the tip of the indenter is 2 mm. The shape of the cross section of the support along the longitudinal direction of the test piece is semicircular, and its radius R2 is 2 mm. The flexural modulus is evaluated by the tangent method. The test is performed at room temperature (25±5°C).

[0034] The composite board 1 may have a bending strength of 2.5 MPa or more. The bending strength may be 2.7 MPa or more, 3.0 MPa or more, 3.2 MPa or more, 3.5 MPa or more, 3.7 MPa or more, 3.8 MPa or more, or even 4.0 MPa or more. The upper limit of the bending strength is, for example, 20 MPa or less. According to the study by the present inventors, the bending strength can contribute to improving both the self-supporting property and the toughness. The composite board 1 further having a bending strength in the above range is particularly suitable for application to wall materials. The bending strength can be determined by the above three-point bending test.

[0035] The fibers 21 may be short fibers. Examples of short fibers are glass wool and mineral fibers. Examples of mineral fibers are rock wool. The substrate 2 may contain at least one selected from the group consisting of glass wool and rock wool. The substrate 2 may be a glass wool board or a rock wool board. The substrate 2 may not be mainly composed of resin, and may not be mainly composed of resin fibers.

[0036] The substrate 2 may be a porous material, including the example of Fig. 1. In this case, a low-density gel body 3 may be present inside the pores 22 of the substrate 2. Examples of the embodiment in which the low-density gel body 3 is present are as described above in the description of Fig. 1.

[0037] The density of the substrate 2 is 32 kg / m 3 or more, 35 kg / m 3 More than 37kg / m 3 More than 40kg / m 3 More than 45kg / m 3 More than 50kg / m 3 More than 55kg / m 3 More than 60kg / m 3 More than 65kg / m 3 More than 70kg / m 3 More than 75kg / m 3 More than 80kg / m 3 More than 85kg / m 3 More than 90kg / m 3 Above 95kg / m 3The upper limit of the density is not limited, but may be, for example, 300 kg / m 3 Less than 250kg / m 3 Below 200kg / m 3 or less. According to the study by the present inventors, the density of the substrate 2 can contribute to improving both the self-supporting property and the toughness of the composite board 1. The composite board 1 including the substrate 2 having the above density is particularly suitable for application to wall materials. The substrate 2 may be a glass wool board or a rock wool board having a density in the above range.

[0038] The thickness of the substrate 2 is, for example, 10 mm or more, and may be 15 mm or more, 20 mm or more, 22 mm or more, 25 mm or more, 27 mm or more, or even 30 mm or more. The upper limit of the thickness is, for example, 300 mm or less, and may be 250 mm or less, 200 mm or less, 150 mm or less, 130 mm or less, 110 mm or less, or even 100 mm or less. The use of a substrate 2 having a thickness of 30 mm or more can contribute, for example, to improving the fire resistance performance of the wall material.

[0039] The low-density gel body 3, as its name indicates, is a low-density solid-phase gel body. The density of the low-density gel body 3 is usually 0.5 g / cm 3 Less than or equal to 0.4 g / cm 3 Below, 0.3g / cm 3 Below, 0.2g / cm 3 Below that, even 0.15g / cm 3 The lower limit of the density is not limited, but may be, for example, 0.05 g / cm 3 That's all.

[0040] The low-density gel body 3 usually has a gel skeleton (hereinafter referred to as skeleton) and pores. The average diameter of the pores is typically 1000 nm or less, and may be 700 nm or less, 500 nm or less, 300 nm or less, or even 100 nm or less. The lower limit of the average diameter is not limited, but is, for example, 10 nm or more. The low-density gel body 3 may have a network structure in which the skeleton and the pores are entangled with each other in a three-dimensional direction. The average diameter of the pores can be specified as the median diameter (d50) by pore distribution measurement using a nitrogen gas adsorption method or the like.

[0041] The porosity of the low-density gel body 3 is, for example, 70 to 99%, and may be 80 to 98%, 85 to 97%, or even 90 to 95%. The porosity can be evaluated by a laser confocal microscope.

[0042] The thermal conductivity of the low-density gel body 3 is, for example, 0.001 to 0.03 W / mK, and may be 0.005 to 0.025 W / mK, or even 0.01 to 0.02 W / mK. The thermal conductivity can be evaluated in accordance with the provisions of Japanese Industrial Standards (hereinafter referred to as JIS) A1412 (steady state method). The value is taken as the value at 25°C. The same applies to the thermal conductivity of the composite board 1.

[0043] The low-density gel body 3 may have a skeleton containing a polyorganosiloxane chain. Having a skeleton containing a polyorganosiloxane chain can contribute to improving the bending properties of the composite board 1.

[0044] The polyorganosiloxane chain is a type of polysiloxane chain containing a siloxane bond. The polysiloxane chain may or may not have a branch of a siloxane bond originating from a silicon (Si) atom constituting the chain. Regarding the constituent units of the polysiloxane chain, the notation of Q unit (the number of organo groups bonded to the Si atom is zero), T unit (the number of organo groups bonded to the Si atom is one), and D unit (the number of organo groups bonded to the Si atom is two) is well known to those skilled in the art. The polyorganosiloxane chain that the skeleton of the low-density gel body 3 may have includes T unit and / or D unit in which an organo group is bonded to a Si atom, and preferably includes T unit. The organo group is a non-polymerizable organic group, and is typically a monovalent group. Examples of the organo group are an alkyl group, an alkenyl group, and an alkynyl group. The number of carbon atoms in these groups is, for example, 1 to 4, and may be 1 to 3, or even 1 to 2. The organo group may be an alkyl group, examples of which are methyl and ethyl groups.

[0045] The polyorganosiloxane chain may have T units as the main constituent units. The polyorganosiloxane chain may not have Q units as the main constituent units, in other words, the low-density gel body 3 may not be silica-based. Having T units as the main constituent units may contribute to improving the bending properties of the composite board 1. In this specification, the main constituent unit means a unit that accounts for 50 mol% or more of all the constituent units that constitute the chain. The proportion of T units may be 60 mol% or more, 65 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, or even 85 mol% or more. The upper limit of the proportion of T units may be, for example, 100 mol% or less, 95 mol% or less, 90 mol% or less, 85 mol% or less, or even 80 mol% or less.

[0046] The polyorganosiloxane chain may have Q units and / or D units. An example of the composition of the polyorganosiloxane chain, expressed in terms of the ratio of each of the Q, T and D units (unit: mole %), is Q:T:D=0-30:60-100:0-20, and may be 0-20:70-90:0-15.

[0047] The low-density gel body 3 may be an aerogel, a xerogel, or a cryogel. The differences in the names aerogel, xerogel, and cryogel come from the differences in the drying methods used to form a solid-phase low-density gel body from a wet gel. A low-density gel body formed by supercritical drying is generally called an aerogel, a low-density gel body formed by normal pressure drying is generally called a xerogel, and a low-density gel body formed by a freeze-drying method is generally called a cryogel.

[0048] The composite board 1 may contain further materials other than the substrate 2 and the low-density gel body 3. An example of the further material is a filler. The composite board 1 may further contain a filler. The filler may be at least one selected from the group consisting of metal hydroxide particles, metal oxide particles, metal salt particles, and carbon particles. The inclusion of a filler that is metal hydroxide particles, metal oxide particles, metal salt particles, and carbon particles, particularly metal hydroxide particles, can contribute to improving the fire resistance performance of the composite board 1. The composite board 1 may contain one or more types of fillers.

[0049] Examples of metal hydroxides that can be used to form the filler include aluminum hydroxide, magnesium hydroxide, iron hydroxide, and copper (II) hydroxide. Examples of metal oxides that can be used to form the filler include iron (III) oxide, iron (II) oxide, manganese ferrite, MnO, MnO 2 , NiO, SnO, Ag 2 O, Bi 2 O 3, titanium oxide, iron-titanium oxide (e.g., ilmenite), aluminum oxide, zirconium silicate, zirconium oxide, and chromium oxide. Examples of metal salts that can form the filler are calcium sulfate (typically a dihydrate) and aluminum sulfate (typically a hydrate). An example of carbon that can form the filler is carbon black. The filler is preferably aluminum hydroxide. According to the studies of the present inventors, aluminum hydroxide has an endothermic effect due to the release of water of crystallization at around 250°C, and is therefore particularly suitable for combination with a low-density gel body 3 having a polyorganosiloxane chain that is usually thermally decomposed at 300°C to 400°C.

[0050] The average particle size of the filler is, for example, 0.1 to 100 μm, and may be 5.0 to 20 μm, 5.0 to 10 μm, or 10 to 20 μm. The average particle size of the filler can be specified as the median size by laser diffraction particle size distribution measurement.

[0051] The amount of filler in the composite board 1 is, for example, 10 to 100 parts by weight, based on 100 parts by weight of the base material 2 and the low-density gel body 3, and may be 20 to 70 parts by weight, 25 to 60 parts by weight, 30 to 50 parts by weight, or even 30 to 40 parts by weight.

[0052] As long as the composite board 1 has a flexural modulus of elasticity of 4.0 MPa or more and a flexural strain at break of 0.05 or more, the configurations of the substrate 2 and the low-density gel body 3 are not limited to the above examples.

[0053] The thermal conductivity of the composite board 1 in the thickness direction is, for example, 0.005 to 0.050 W / mK, and may be 0.008 to 0.035 W / mK, 0.01 to 0.03 W / mK, 0.01 to 0.027 W / mK, or even 0.015 to 0.025 W / mK. The composite board 1 may be a heat insulating board. The thermal conductivity of commercially available glass wool boards is at least about 0.028 W / mK, and the thermal conductivity of rock wool boards is at least about 0.045 W / mK.

[0054] The density of the composite board 1 is, for example, 100 to 350 kg / m 3 and 150 to 340 kg / m 3 , 175~325kg / m 3 , 200~300kg / m 3 , 225~275kg / m 3 may be also possible.

[0055] The water absorption of the composite board 1 is, for example, 0.1 to 3 g / cm 2 and 0.2 to 2.5 g / cm 3 , 0.3~2g / cm 2 , 0.4~1.5g / cm 2 , and even 0.5 to 1.3 g / cm 2 The water absorption of commercially available glass wool boards and rock wool boards is usually 30 g / cm 2 That is all. The composite board 1 with low water absorption is particularly suitable for application to exterior walls. The water absorption can be measured in accordance with the provisions of JIS A9521. However, the shape of the test piece should be a rectangular parallelepiped with a length of 50 mm, a width of 50 mm, and a thickness of 10 mm.

[0056] The composite board 1 can have performance equivalent to the fire-resistant structure defined in the Building Standards Act. For example, when the composite board 1 is 30 mm thick, it can have heat-shielding and / or flame-shielding properties when one of its main surfaces is heated for 30 minutes and then left for 1 hour and 30 minutes after heating (three times the heating time) based on the standard heating curve defined in ISO834. Heat-shielding properties refer to the property that the temperature rise of the unheated surface, based on the temperature before heating, is kept to an average of 140 K or less and a maximum of 180 K or less. Flame-shielding properties refer to the absence of flame eruptions on the unheated surface for more than 10 seconds.

[0057] The shape of the composite board 1 is typically square or rectangular when viewed perpendicularly to its main surface. However, the shape is not limited to the above examples. The composite board 1 may be processed into a desired shape, for example, by performing mechanical processing such as cutting or milling on the composite board 1 manufactured into a rectangular shape.

[0058] The thickness of the composite board 1 is, for example, 10 mm or more, and may be 15 mm or more, 20 mm or more, 22 mm or more, 25 mm or more, 27 mm or more, or even 30 mm or more. The upper limit of the thickness is, for example, 300 mm or less, and may be 250 mm or less, 200 mm or less, 150 mm or less, 130 mm or less, 110 mm or less, or even 100 mm or less.

[0059] The area of ​​the composite board 1 is 0.1 m 2 More than 0.5m 2 More than 1m 2 More than 5m 2 More than 10m 2 More than 20m 2 Over 25m 2 More than 50m 2 There is no upper limit to the area, but it is, for example, 80 m 2 The long side of the composite board 1 may be 0.1 m or more, 0.5 m or more, 1 m or more, 2 m or more, 3 m or more, 4 m or more, 5 m or more, or even 8 m or more. There is no upper limit to the long side, but it is, for example, 12 m or less. The composite board 1 can be self-supporting even when it has the above area.

[0060] An example of the application of the composite board 1 is a wall material for a building. In other words, the composite board 1 may be used as a wall material for a building. The wall material may be an exterior wall or an interior wall, but the composite board 1, which may have a low thermal conductivity, is particularly suitable for application to an exterior wall. When the composite board 1 is applied to a wall material, it may be embedded in the wall material as an insulating board, or may be applied as a wall material in a state combined with other members such as decorative materials. In addition, the composite board 1 can also be applied to a wall material as a composite panel using the composite board 1 as a core material. However, the application of the composite board 1 is not limited to the above examples.

[0061] [Manufacturing method of composite board] The following describes a method for producing the composite board 1. In the following example, the low-density gel body 3 is formed by the progress of a sol-gel reaction on a precursor compound. However, the method for producing the composite board 1 is not limited to the following example.

[0062] The manufacturing method of this embodiment includes forming a wet gel by immersing a substrate 2 in a solution containing a sol of a precursor compound having a hydrolyzable functional group (hereinafter referred to as the solation solution) and proceeding with gelation of the sol while the substrate 2 is immersed in the solution (gelation process), and drying the wet gel to form a composite board 1 including the substrate 2 and a low-density gel body 3 composited with the substrate 2 (drying process).

[0063] (Gelling process) In the manufacturing method of this embodiment, the low-density gel body 3 is manufactured through the formation of a wet gel, which is a gel of a precursor compound. The wet gel can be formed by soling a precursor compound by a hydrolysis reaction, and further gelling the soled precursor compound by a polycondensation reaction. The soling and gelling may proceed independently or overlappingly. When proceeding independently, the soling and gelling may proceed continuously, or may proceed with a time lag between the completion of the soling and the start of the gelling. In addition, in the manufacturing method of this embodiment, the gelling is allowed to proceed while the base material 2 is immersed in the soling solution. However, the immersion of the base material 2 can be carried out at any timing, regardless of the degree of soling of the precursor compound. In other words, the base material 2 may be immersed in a solution before soling (hereinafter referred to as a precursor solution), or in a soling solution in which soling has progressed partially or completely. In a typical example, the base material 2 is immersed at the point when soling has progressed partially or completely.

[0064] The substrate 2 is preferably immersed in the solution so that the solution penetrates into the substrate 2. When the substrate 2 is a porous material, the solution may be immersed in the pores of the substrate 2. In a preferred example, the substrate 2 is placed in a container such as a tray or a pad, and the solution is poured into the container. A container corresponding to the desired shape and size of the low-density gel body 3 may be selected, and the container may be used as a mold to allow gelation to proceed. To aid penetration, mechanical vibration or ultrasonic waves may be applied to at least one selected from the group consisting of the container, the solution, and the substrate 2.

[0065] 1.Solation The hydrolyzable functional group of the precursor compound is, for example, an alkoxy group having 1 to 4 carbon atoms. However, the functional group is not limited to the above examples. The functional group may be a methoxy group or an ethoxy group. The methoxy group and the ethoxy group are particularly suitable for stable hydrolysis and polycondensation reactions.

[0066] The precursor compound may be a silicon compound. An example of the silicon compound is an alkoxysilane. Examples of the silicon compound that can be used to form Q units through the gelation process are tetramethoxysilane (TMOS), tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. Examples of the silicon compound that can be used to form T units are methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, propyltriethoxysilane, pentyltriethoxysilane, hexyltriethoxysilane, and octyltriethoxysilane. Examples of the silicon compound that can be used to form D units are dimethyldimethoxysilane, diethyldimethoxysilane, and diisobutyldimethoxysilane. However, the precursor compound and the silicon compound are not limited to the above examples.

[0067] The solation is usually carried out on a precursor solution. The precursor solution contains one or more precursor compounds. The precursor solution may contain two or more precursor compounds depending on the desired composition of the low-density gel body 3. For example, the precursor solution may contain a silicon compound capable of forming T units, and may further contain a silicon compound capable of forming Q units and / or a silicon compound capable of forming D units. The contents of T units, Q units and D units in the low-density gel body 3 can be controlled by the type and content of the precursor compounds contained in the precursor solution.

[0068] When two or more kinds of precursor compounds are contained in the precursor solution, the total content of the precursor compounds is, for example, 10 to 70% by volume, and may be 20 to 60% by volume, or even 30 to 50% by volume.

[0069] The solvent of the precursor solution is not limited as long as the hydrolysis reaction of the precursor compound can proceed. Examples of the solvent are water, methanol, ethanol, 2-propanol, benzyl alcohol, formamide, N,N-dimethylformamide, and dimethylsulfoxide. The solvent may be a mixture of these. Examples of the preferred solvent are water, methanol, ethanol, 2-propanol, and a mixture of these. The above-mentioned solvents are also suitable for the polycondensation reaction.

[0070] The precursor solution may contain a catalyst (solation catalyst) that promotes the hydrolysis reaction. An example of the solation catalyst is an acid. Examples of the acid catalyst are inorganic acids such as hydrochloric acid, nitric acid, and sulfuric acid; and organic acids such as formic acid, acetic acid, and oxalic acid. For more stable progress of the hydrolysis reaction, organic acids are particularly suitable. The precursor solution may contain one or more types of acid catalysts.

[0071] The concentration of the solation catalyst added to the precursor solution is, for example, 0.0001 mol / L to 0.1 mol / L, and may be 0.0005 mol / L to 0.05 mol / L, or 0.001 mol / L to 0.01 mol / L, relative to the entire solution.

[0072] As long as the low-density gel body 3 is formed, the precursor solution may contain materials other than those mentioned above.

[0073] The temperature for the solation is, for example, 0 to 120° C., and may be 0 to 60° C. The time required for the solation to be completed varies depending on the composition of the precursor solution, and is, for example, 0.5 to 1.5 hours, and may be 0.75 to 1 hour.

[0074] 2. Gelation The gelation is allowed to proceed in a state where the substrate 2 is immersed in a solution containing a sol of a precursor compound (sol solution). The solation solution may contain the precursor compound before it is solated.

[0075] Examples of the solvent for the solation solution are the same as the examples of the solvent for the precursor solution. The same solvent may be used for the solation and gelation.

[0076] The solated solution may contain a catalyst (gelling catalyst) that promotes the polycondensation reaction. An example of the gelling catalyst is a base. Examples of the base catalyst include ammonia; ammonium compounds such as ammonium hydroxide, ammonium fluoride, ammonium chloride, and ammonium bromide; alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, and cesium hydroxide; basic sodium phosphates such as sodium metaphosphate, sodium pyrophosphate, and sodium polyphosphate; allylamine, diallylamine, triallylamine, isopropylamine, diisopropylamine, ethylamine, diethylamine, triethylamine, 2-ethylhexylamine, 3-ethoxypropylamine, diisobutylamine, and 3-(diethylamino)propylamine. Aliphatic amines such as propylamine, di-2-ethylhexylamine, 3-(dibutylamino)propylamine, tetramethylethylenediamine, t-butylamine, sec-butylamine, propylamine, 3-(methylamino)propylamine, 3-(dimethylamino)propylamine, 3-methoxyamine, dimethylethanolamine, methyldiethanolamine, diethanolamine, and triethanolamine; and nitrogen-containing heterocyclic compounds such as morpholine, N-methylmorpholine, 2-methylmorpholine, piperazine and its derivatives, piperidine and its derivatives, and imidazole and its derivatives. The solated solution may contain one or more types of base catalysts.

[0077] The base catalyst may be a compound that generates a basic substance when heated. The compound may be added to the precursor solution in advance. In this case, the solution may be heated at any stage in which the solation has progressed, for example, at the stage in which the solation has been completed, to generate a basic substance, which may then be used to advance the polycondensation reaction. An example of the above compound is a nitrogen compound. Examples of the nitrogen compound include amide compounds such as urea, formamide, N-methylformamide, N,N-dimethylformamide, acetamide, N-methylacetamide, and N,N-dimethylacetamide; and heterocyclic compounds such as hexamethylenetetramine. Among these, urea is particularly suitable from the viewpoint of increasing the rate of gelation. Urea usually generates ammonia when the temperature of the solution is about 55°C or higher.

[0078] The amount of the gelling catalyst in the solated solution is, for example, 0.5 to 10 parts by weight, or may be 1 to 5 parts by weight, per 100 parts by weight of the precursor compound and its sol. When a compound that generates a basic substance upon heating is used, the amount of the compound may be adjusted so that the amount of the generated basic substance falls within the above range.

[0079] The gelation temperature is, for example, 0 to 120° C., and may be 0 to 60° C. The time required for the gelation to be completed varies depending on the composition of the solated solution, and is, for example, 1 to 120 hours, and may be 1 to 72 hours.

[0080] As long as the low-density gel body 3 is formed, the solation solution may contain materials other than those mentioned above.

[0081] An example of the other material is a surfactant. The surfactant can contribute to the formation of the gel skeleton and pores due to the progression of the phase separation process. Examples of the surfactant are nonionic surfactants, anionic surfactants, and cationic surfactants. An example of the nonionic surfactant is a nonionic triblock copolymer consisting of ethylene oxide and propylene oxide chains. Examples of the triblock copolymer are Pluronic (registered trademark) F-127, L-64, P-105, P-94, and F-68. Examples of the cationic surfactant are cetyltrimethylammonium bromide and cetyltrimethylammonium chloride. However, the surfactant is not limited to the above examples.

[0082] The amount of the surfactant to be added is, for example, 0.001 to 100 parts by weight, and may be 0.01 to 90 parts by weight, or further 0.1 to 80 parts by weight, per 100 parts by weight of the precursor compound and its sol.

[0083] As long as the formation of the low-density gel body 3 is possible, the surfactant may be mixed in advance into the precursor solution.

[0084] Another example of the other material is an additive such as a filler, etc. As long as the low-density gel body 3 can be formed, the additive may be mixed in advance in the precursor solution.

[0085] 3. Aging In the manufacturing method of this embodiment, the wet gel formed by gelation may be aged (ripened). Aging can contribute to improving the final polycondensation rate. The aging temperature is, for example, 0 to 120°C, and may be 60 to 100°C. The aging time is, for example, 24 to 120 hours, and may be 48 to 72 hours.

[0086] (drying process) In the drying step, the wet gel formed through the gelling step is dried to form a low-density gel body 3. A known drying method for obtaining a low-density gel body can be applied to dry the wet gel. Examples of the drying method include supercritical drying, atmospheric drying, and freeze drying.

[0087] In the supercritical drying, a fluid in a supercritical state is used. Examples of the fluid include a carbon dioxide fluid, a methanol fluid, and a water fluid. Before the supercritical drying, the wet gel may be subjected to solvent exchange.

[0088] In the manufacturing method of this embodiment, the wet gel may be dried by drying at normal pressure. The temperature of the drying at normal pressure is not limited, but may be, for example, 20 to 120° C., or 40 to 60° C. Before drying at normal pressure, the wet gel may be subjected to solvent substitution.

[0089] The solvent replacement may be performed for the purpose of removing catalysts, surfactants, etc., removing by-products, or suppressing damage to the low-density gel body 3 during drying. When performing the solvent replacement for multiple purposes, the replacement with different solvents for each purpose may be performed multiple times.

[0090] Examples of the solvent used to remove the catalyst or additives include alcohols such as methanol, ethanol, n-propanol, isopropanol, 1-butanol, etc. A mixed solvent of two or more kinds of solvents may also be used.

[0091] An example of a solvent used to prevent damage to the low-density gel body 3 during drying is a solvent with low surface tension, for example, a solvent with a surface tension of 45 mN / m or less at 20°C. Examples of such solvents are dimethyl sulfoxide, cyclohexane, isopropanol, heptane, and pentane. A mixed solvent of two or more solvents may also be used. The surface tension may be 40 mN / m or less, 35 mN / m or less, 30 mN / m or less, 25 mN / m or less, 20 mN / m or less, or even 15 mN / m or less. The lower limit of the surface tension is, for example, 5 mN / m or more.

[0092] The manufacturing method of this embodiment may include any step other than those described above, so long as the method can obtain a low-density gel body 3. An example of such a step is a washing step.

[0093] [Composite panel] An example of the composite panel of this embodiment is shown in FIG. 2A and FIG. 2B. FIG. 2B is a cross-sectional view showing the cross section 2B-2B of FIG. 2A. The composite panel 11 of FIG. 2A and FIG. 2B includes the composite board 1 of this embodiment, a front material 12 arranged on one main surface of the composite board 1, and a back material 13 arranged on the other main surface. The composite panel 11 further includes first fillers 15A, 15B, a second filler 16, and a sealing material 17. The first fillers 15A, 15B, and the second filler 16 are members that have the function of filling the gaps in the fitting parts between the adjacent composite panels 11 when a plurality of composite panels 11 are arranged to form a wall of a building. The strength and shape retention of the composite panel 11 as a wall material are mainly provided by the composite board 1. In other words, the composite board 1 is the main member of the composite panel 11. The composite board 1 may account for 90% or more, preferably 95% or more, 98% or more, or even 99% or more of the volume of the composite panel 11. The composite board 1 may account for 90% or more, preferably 95% or more, 98% or more, or even 99% or more of the weight of the composite panel 11. The composite panel 11 in Figures 2A and 2B is a sandwich panel having the composite board 1 as a core material.

[0094] The surface material 12 and the backing material 13 are usually in the form of a sheet and can function as a surface layer of the composite panel 11. Various metals, resins, and composite materials can be used for the surface material 12 and the backing material 13. Examples of metals are steel, aluminum, and stainless steel. Examples of resins are polycarbonate, polypropylene, and polyethylene. An example of a composite material is fiber-reinforced plastic (FRP). The use of aluminum, resin, and composite materials can contribute to reducing the weight of the composite panel 11. A water-resistant material may be used for the surface material 12 and / or the backing material 13. The composite panel 11 having a water-resistant surface layer is particularly suitable for application to an exterior wall. Examples of water-resistant materials are plated steel sheets such as galvalume (aluminum-zinc alloy plated) steel sheets and zinc-plated steel sheets, and stainless steel sheets. The surfaces of the surface material 12 and the backing material 13 may be surface-treated as necessary. Examples of surface treatments include painting with various resins, antifouling paint, and other painting treatments.

[0095] The thickness of the front surface material 12 and the back surface material 13 is, for example, 0.1 to 1 mm, and may be 0.2 to 0.8 mm, or further 0.3 to 0.7 mm.

[0096] The surface layer may be disposed on at least one surface, typically the main surface, of the composite board. In the example of Fig. 2A and Fig. 2B, the surface layer is disposed on both main surfaces of the composite board 1. In addition, the surface layer is not limited to the above example, and may be, for example, a coating film.

[0097] The front surface material 12 and / or the back surface material 13 may be bonded to the composite board 1. For bonding, various adhesives such as a rubber-based adhesive, a urethane-based adhesive, and an acrylic-based adhesive can be used.

[0098] Examples of the first fillers 15A and 15B are gypsum board, fiber-mixed calcium silicate board, wood wool cement board, and wood cement board. Examples of the second filler 16 are ceramic fiber, alkaline earth silicate wool (biosoluble fiber), alumina fiber, and rock wool felt. Examples of the sealant 17 are various rubbers and elastomers.

[0099] The composite panel 11 may have the same thermal conductivity in the thickness direction as the composite board 1. The composite panel 11 may be a heat insulating panel.

[0100] The composite panel 11 can have performance equivalent to the fire-resistant structure in the Building Standards Act. For example, when the composite panel 11 has a thickness of 30 mm, it can have the above-mentioned heat insulation property and / or flame insulation property when one main surface is heated for 30 minutes and left for 1 hour and 30 minutes after heating based on the standard heating curve defined in ISO834.

[0101] The shape of the composite panel 11 is typically a square or a rectangle when viewed perpendicularly to its main surface, although the shape is not limited to the above examples.

[0102] The thickness of the composite panel 11 is, for example, 10 mm or more, and may be 20 mm or more, 30 mm or more, 40 mm or more, or even 50 mm or more. The upper limit of the thickness is, for example, 300 mm or less, and may be 250 mm or less, 200 mm or less, 150 mm or less, 130 mm or less, 110 mm or less, or even 100 mm or less.

[0103] The area of ​​the composite panel 11 is 0.1 m 2 More than 0.5m 2 More than 1m 2 More than 5m 2 More than 10m 2 More than 20m 2 Over 25m 2 More than 50m 2 There is no upper limit to the area, but it is, for example, 80 m 2 The long side of the composite panel 11 may be 0.1 m or more, 0.5 m or more, 1 m or more, 2 m or more, 3 m or more, 4 m or more, 5 m or more, or even 8 m or more. The upper limit of the long side is not limited, but is, for example, 12 m or less.

[0104] The composite panel 11 can have the same structure as a known sandwich panel, so long as it has the composite board 1 as a core material.

[0105] An example of the application of the composite panel 11 is a wall material for a building. In other words, the composite panel 11 may be used as a wall material for a building. The wall material may be an exterior wall or an interior wall, but the composite panel 11 including the composite board 1 that may have low thermal conductivity is particularly suitable for application to an exterior wall. However, the application of the composite panel 11 is not limited to the above example.

[0106] [Manufacturing method of composite panels] In the manufacturing method of the composite panel of the present embodiment, a surface layer is disposed on at least one surface of the composite board 1 to form the composite panel 11. The composite panel 11 may be manufactured according to a known manufacturing method for a sandwich panel, except that the composite board 1 is used as a core material. EXAMPLES

[0107] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.

[0108] [Preparation of sol solution] Tetramethoxysilane (TMOS) was prepared as a precursor compound capable of forming Q units through the gelation process, methyltrimethoxysilane (MTMS) was prepared as a precursor compound capable of forming T units, and dimethyldimethoxysilane (DMDMS) was prepared as a precursor compound capable of forming D units.

[0109] 70 mL of acetic acid solution with a concentration of 5 mM, 30 g of powdered urea, and 6 g of Pluronic F-127 (manufactured by Sigma-Aldrich), a nonionic surfactant, were mixed and stirred to obtain a uniform solution. Next, the precursor compound (50 mL in total) was added in the ratio (volume basis) shown in Table 1 below, and stirring was continued for 30 minutes at room temperature. As described above, solated solutions A1 to A5 were prepared by solvating the precursor compound by stirring in the presence of an acid catalyst. In addition, solated solution A6 was prepared in the same manner as above, except that aluminum hydroxide particles (manufactured by Armolix, B-303) were further added as a filler about 30 minutes after the precursor compound was added. The amount of aluminum hydroxide particles was 35 parts by weight per 100 parts by weight of the precursor compound. The average particle size of the aluminum hydroxide particles was 6.5 μm.

[0110] [Table 1]

[0111] [Formation of composite board] A rectangular glass wool board (length 100 mm x width 100 mm x thickness 11 mm) was placed on a rectangular pad as a substrate, and each of the prepared solvation solutions was poured into the substrate so that the entire substrate was covered with the solvation solution, immersing the substrate. During immersion, the pad was vibrated by hand to ensure that the solvation solution was sufficiently permeated into the substrate. The glass wool board had a density of 96 kg / m 3(hereinafter referred to as Glass Wool I; Magisover, Magboard) or density 16kg / m 3 (hereinafter referred to as Glass Wool II; manufactured by Asahi Fiberglass, Aclear) was used.

[0112] Next, the whole was heated to 60°C to generate ammonia from urea, and the mixture was left for 5 hours to promote polycondensation and gelation, forming a wet gel. The wet gel was then aged by leaving it at 60°C for 3 days. Next, the mixture was subjected to solvent replacement with methanol, solvent replacement with isopropanol, and solvent replacement with heptane in order, and then dried at normal pressure and 120°C for 8 hours to form seven types of composite boards B1 to B7, including a substrate and a low-density gel body composited with the substrate. For each solvent replacement, a solvent was used in an amount 5 times the volume of the substrate. The solvent replacement was performed at room temperature. The shape and size of the composite board formed were almost the same as those of the substrate used. Table 2 below shows the combination of the sol solution and the glass wool board in each composite board.

[0113] [Table 2]

[0114] The bending properties and thermal conductivity were evaluated for the composite board prepared above, and for reference examples, Pyrogel XT manufactured by Aspen Aerogel, glass wool board I alone, and glass wool board II alone. The bending properties were evaluated by the 3-point bending test described above, in terms of bending modulus, bending breaking strain, and bending strength. For the 3-point bending test, an autograph manufactured by Shimadzu Corporation was used. The shape of the test piece was a rectangular parallelepiped with a length of 50 mm, a width of 10 mm, and a thickness of 5 mm. The load direction in the 3-point bending test was perpendicular to the layered surface of the fibers. The thermal conductivity was evaluated by the method described above. According to the product description by Aspen Aerogel, Pyrogel XT is an aerogel bracket in which silica-based aerogel is impregnated into a nonwoven fabric of long glass fibers.

[0115] The evaluation results are shown in Table 3 below. The stress-strain curves obtained by the three-point bending test are shown in Figure 3. Note that the bending properties of Reference Example 3 could not be measured because the flexibility of the glass wool board II was very high and it was not possible to set a test piece in the measuring device.

[0116] [Table 3]

[0117] As shown in Table 3 and FIG. 3, the composite boards of the examples were excellent in the balance of the elastic modulus and the breaking strain, and were suitable for use as wall materials. In addition, the composite boards of Examples 2 and 3 had a thermal conductivity of about 0.02 W / mK and were also excellent in heat insulation. It is estimated that the thermal conductivity of the composite board is mainly affected by its pore structure, not by the composition of the low-density gel body, when the base material is the same. For this reason, it was estimated that the thermal conductivity of other examples, which were formed under the same manufacturing conditions and were considered to have similar pore structures, was about 0.02 W / mK. On the other hand, the composite board of the comparative example had insufficient either the elastic modulus or the breaking strain, and was not suitable for wall materials. In addition, while the composite boards of the examples had a bending modulus sufficient to be self-supporting, the bending modulus of the composite board of Comparative Example 2 was low and did not have self-supporting properties. Although the thermal conductivity of the Pyrogel XT of Reference Example 1 was lower than that of the glass wool board of Reference Example 2, the elastic modulus was significantly low and was not suitable for wall materials. The glass wool board of Reference Example 2 had both an elastic modulus and a breaking strain that were suitable for a wall material, but was poor in thermal conductivity.

[0118] [Other characteristics] (density) The densities of the composite boards of Examples 2 and 3 were 259 kg / m 3 and 269 kg / m 3 The density was evaluated by the method described above.

[0119] (Water absorption) The water absorption of the composite boards of Examples 2 and 3 was 1.0 g / cm 3 and 0.5 g / cm3 The water absorption of Pyrogel XT in Reference Example 1 was 1.4 g / cm 2 The water absorption of the glass wool board of Reference Example 2 was 36.7 g / cm 3 The water absorption was evaluated by the method described above.

[0120] (Fireproof performance) The composite board of Example 2, when 30 mm thick, had flame-resistant properties when one of its main surfaces was heated for 30 minutes and left for 1.5 hours after heating based on the standard heating curve defined in ISO 834. The composite board of Example 5, which contained a filler, when 30 mm thick, had both heat-resistant and flame-resistant properties when one of its main surfaces was heated for 30 minutes and left for 1.5 hours after heating based on the standard heating curve defined in ISO 834. [Industrial Applicability]

[0121] The composite board and composite panel of the present invention are suitable for use as wall materials in buildings. [Explanation of symbols]

[0122] 1 Composite board 2 Base material 3. Low density gel body 11 Composite Panel 12 Surface material (surface layer) 13 Backing material (surface layer)

Claims

1. The present invention includes a substrate and a low-density gel body composited with the substrate, A composite board having a flexural modulus of 4.0 MPa or more and a flexural fracture strain of 0.05 or more.

2. The composite board according to claim 1 , wherein the composite board has a flexural strength of 2.5 MPa or more.

3. The substrate is a porous material, 2. The composite board according to claim 1, wherein the low-density gel body is present inside pores of the substrate.

4. The composite board of claim 1 , wherein the substrate comprises at least one selected from the group consisting of glass wool and rock wool.

5. The density of the substrate is 32 kg / m 3 The composite board according to claim 1 .

6. 2. The composite board of claim 1, wherein the low density gel body has a backbone that includes polyorganosiloxane chains.

7. 7. The composite board of claim 6, wherein the polyorganosiloxane chain has T units as the main building blocks.

8. The composite board of claim 1 further comprising a filler.

9. 9. The composite board according to claim 8, wherein the filler is at least one selected from the group consisting of metal hydroxide particles and metal oxide particles.

10. 2. The composite board according to claim 1, which is used as a wall material for buildings.

11. A composite board according to any one of claims 1 to 10; a surface layer disposed on at least one surface of the composite board; A composite panel comprising:

12. The composite panel according to claim 11, which is used as a wall material for buildings.

13. A method for producing a composite board according to any one of claims 1 to 10, comprising the steps of: forming a wet gel by immersing the substrate in a solution containing a sol of a precursor compound having a hydrolyzable functional group and proceeding with gelation of the sol in a state where the substrate is immersed in the solution; drying the wet gel to form the composite board comprising the substrate and a low density gel body composited with the substrate; A method for producing a composite board, comprising:

14. The method for producing a composite board according to claim 13, wherein the precursor compound is a silicon compound.

15. The method for producing a composite board according to claim 13, wherein the wet gel is dried by drying at normal pressure.

16. A method for producing the composite panel according to claim 11, and disposing a surface layer on at least one surface of the composite board.

Citation Information

Patent Citations

  • Aerogel product and preparation method thereof

    CN113896205A

  • Segmented gel composite material and rigid panels made therefrom

    JP2022104991A

  • Core material for vacuum insulation panel and manufacturing method for same

    WO2011111939A2

  • Steel sheet for sandwich panel and urethane foam sandwich panel

    JP1998226010A

  • Silica aerogel

    US4402927A